The ever expanding scope of electrospray mass spectrometry—a 30 year journey - Matthias Mann (Nature Portfolio, 2019)
John Fenn’s electrospray mass spectrometry (ESMS) was awarded the chemistry Nobel Prize in 2002 and is now the basis of the entire field of MS-based proteomics. Technological progress continues unabated, enabling single cell sensitivity and clinical applications.